Pengaruh Stres Kerja, Beban Kerja dan Konflik Kerja terhadap Semangat Kerja Karyawan di Perumda Air Minum Tirta Anai Unit Batang Anai Kabupaten Padang Pariaman - Abaharis, Henryanto; Dasril, Afifah Meida (ARZUSIN, 2025)
Employee morale is a key factor in achieving organizational goals, but is often disrupted by work stress, excessive workload, and work conflicts that have not been managed optimally. This study aims to analyze the effect of work stress, workload, and work conflict on employee morale at PERUMDA Air Minum Tirta Anai Unit Batang Anai Padang Pariaman Regency. This research uses a quantitative approach with descriptive methods. The research sample amounted to 38 people who were the entire population of employees in the unit. Data were collected through observations, interviews, and questionnaires arranged on a Likert scale, then analyzed using multiple linear regression. Validity and reliability tests were conducted to ensure the validity of the instrument, and classical assumption tests (normality, multicollinearity, and heteroscedasticity) to ensure the feasibility of the regression model. The results showed that work stress and workload have a positive and significant effect on employee morale, while work conflict has no significant effect. The conclusion of this study is that good stress management and workload distribution can improve morale, while work conflict, although not significant, still needs to be monitored so that it does not develop into a psychological barrier in the work environment.